Applications of Nanotechnology in Green Chemistry - Rawya Z Al-khayat; Ammar Gh. Ameen AL-dabbagh; Seba S. Mohammed; Raya Doraid Mohammed (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Nanotechnology is the science of present and future, it has different physical, chemical, biological preparation methods, it has many applications in green chemistry, agriculture, industry, electronics, environmental pollution. Gold, silver, zinc oxide and titanium dioxide nanoparticles are among most important particles that have many advantages and uses.